2022
DOI: 10.3390/ijms23105713
|View full text |Cite
|
Sign up to set email alerts
|

CtpB Facilitates Mycobacterium tuberculosis Growth in Copper-Limited Niches

Abstract: Copper is required for aerobic respiration by Mycobacterium tuberculosis and its human host, but this essential element is toxic in abundance. Copper nutritional immunity refers to host processes that modulate levels of free copper to alternately starve and intoxicate invading microbes. Bacteria engulfed by macrophages are initially contained within copper-limited phagosomes, which fuse with ATP7A vesicles that pump in toxic levels of copper. In this report, we examine how CtpB, a P-type ATPase in M. tuberculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…However, when there is a rapid increase in copper levels, it has been observed that ctpB-knockout M. tuberculosis-infected mice exhibit increased resistance to copper, which enhances the efflux of copper. (Shey-Njila et al, 2022).…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%
“…However, when there is a rapid increase in copper levels, it has been observed that ctpB-knockout M. tuberculosis-infected mice exhibit increased resistance to copper, which enhances the efflux of copper. (Shey-Njila et al, 2022).…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%
“…The balance of micronutrients is important for M.tb survival. The bacterial ATPase CtpB was found to be important for the regulation of copper levels and the optimal growth of M.tb both in vitro and in the mouse model [ 136 ]. The ability of M.tb to mutate and overcome the loss of the ESX-3 type VII secretion system, involved in iron acquisition, and thus restore virulence, has also been described in the mouse model [ 137 ].…”
Section: Other Microbiological Factorsmentioning
confidence: 99%